Current trends in drug metabolism and pharmacokinetics - Yuhua Li; Qiang Meng; Mengbi Yang; Dongyang Liu; Xiangyu Hou; Lan Tang; Xin Wang; Yuanfeng Lyu; Xiaoyan Chen; Kexin Liu; Ai-Ming Yu; Zhong Zuo; et al. (Elsevier, 2019)
Pharmacokinetics (PK) is the study of the absorption, distribution, metabolism, and excretion (ADME) processes of a drug. Understanding PK properties is essential for drug development and precision medication. In this review we provided an overview of recent research on PK with focus on the following aspects: (1) an update on drug-metabolizing enzymes and transporters in the determination of PK, as well as advances in xenobiotic receptors and noncoding RNAs (ncRNAs) in the modulation of PK, providing new understanding of the transcriptional and posttranscriptional regulatory mechanisms that result in inter-individual variations in pharmacotherapy; (2) current status and trends in assessing drug-drug interactions, especially interactions between drugs and herbs, between drugs and therapeutic biologics, and microbiota-mediated interactions; (3) advances in understanding the effects of diseases on PK, particularly changes in metabolizing enzymes and transporters with disease progression; (4) trends in mathematical modeling including physiologically-based PK modeling and novel animal models such as CRISPR/Cas9-based animal models for DMPK studies; (5) emerging non-classical xenobiotic metabolic pathways and the involvement of novel metabolic enzymes, especially non-P450s. Existing challenges and perspectives on future directions are discussed, and may stimulate the development of new research models, technologies, and strategies towards the development of better drugs and improved clinical practice. KEY WORDS: Pharmacokinetics, Drug metabolism, Drug-drug interactions, Modeling, Metabolizing enzymes, Transporters, Nuclear receptors, Noncoding RNAs